Hubungan Antara Manajemen Diri dengan Prokrastinasi Akademik pada Mahasiswa Anggota MUEC UMS - Hardiyanti, Astria; , Dra. Partini M. Si (2016)
Student must be good at academic and organization, in order to gain a potential and skill. Student that join the organization, is expected to have skill and potential that better than before. In fact, the students that join in organization haveless attention about their academic task and give more attention on about something that not important or just to find the happiness that called acode mic procrastination. One of factor that affecting the academic procrastination in self management. This research aimed to know the raletionship between self management and academic procrastination in member of MUEC. The hypothesis in this research in there is negative relationship between self management with academic procrastination in mamber of MUEC. Subjects in this reseach are 70 activist of MUEC UMS and use the scale of self management and academic procrastination. In this research were chosen by non random sampling. The analysis result with product moment analysis corelation from Pearson, obtainted the result correlation coefficient of rxy = - 0,738 with the sig 0,000 (p<0,01) if means there is negative relationship. That significant between self management and academic procrastination the affective contribution between self management anf academic prokcrastination is 54,46 %.